SARS-CoV-2 RBD protein enhances the oncolytic activity of the vesicular stomatitis virus - Alkayyal, Almohanad A.; Ajina, Reham; Cacciabue, Marco; Alkayyal, Aaesha A.; Saeedi, Nizar H.; Hussain Alshehry, Taofik; Kaboha, Feras; Alotaibi, Mohammed A.; Zaidan, Nada; Shah, Khalid; Alroqi, Fayhan; Bakur Mahmoud, Ahmad (Frontiers in Immunology, 2023)
Despite recent advances in the research on oncolytic viruses (OVs), a better understanding of how to enhance their replication is key to improving their therapeutic index. Understanding viral replication is important to improve treatment outcomes based on enhanced viral spreading within the tumor milieu. The VSV-Δ51 oncolytic virus has been widely used as an anticancer agent with a high selectivity profile. In this study, we examined the role of the SARS-CoV-2 spike protein receptor-binding domain (RBD) in enhancing VSV-Δ51 viral production and oncolytic activity. To test this hypothesis, we first generated a novel VSV-Δ51 mutant that encoded the SARS-COV-2 RBD and compared viral spreading and viral yield between VSV-Δ51-RBD and VSV-Δ51 in vitro. Using the viral plaque assay, we demonstrated that the presence of the SARS-CoV-2 RBD in the VSV-Δ51 genome is associated with significantly larger viral plaque surface area and significantly higher virus titers. Subsequently, using an ATP release-based assay, we demonstrated that the SARS-CoV-2 RBD could enhance VSV-Δ51 oncolytic activity in vitro. This observation was further supported using the B16F10 tumor model. These findings highlighted a novel use of the SARS-CoV-2 RBD as an anticancer agent.